Biometric characterization and tetrazolium test in Campomanesia phaea O. Berg. Landrum seeds - Aparecida Leonir da Silva; Mariane Jeronimo Forte; Angelo Pedro Jacomino; Victor Augusto Forti; Simone Rodrigues da Silva (Journal of Seed Science, 2021)
ABSTRACT: Campomanesia phaea has commercial interest because its fruits are used in the manufacture of several products, besides its high nutritional potential. Nevertheless, it has low germination potential and there is not much information in the literature. The aim of this study was to perform a biometric characterization and to establish the tetrazolium test for cambuci seeds. Seeds obtained from two collection periods were subjected to biometric evaluations (seed length, thickness, width and mass), water content, determination of the soaking curve and tetrazolium test. The soaking curve was performed with non-scarified seeds and seeds subjected to two scarification methods, mechanical and chemical. The tetrazolium test was performed soaking the seeds in a solution of 2, 3, 5 triphenyl tetrazolium chloride salt at 0.75, 1.00 and 1.50% for 4, 8 and 12 hours. After this period, the seeds were categorized as viable and non-viable. It was concluded that the cambuci seeds presented biometric differences between the two collection periods, because of the different water contents. There was no difference in the soaking curve among the three treatments tested and the solution of 0.75% for four hours in a water bath at 38 oC was considered the best for performing the tetrazolium test.